The bidirectional phase-shifting effects of melatonin on the arginine vasopressin secretion rhythm in rat suprachiasmatic nuclei in vitro - Svobodova, Irena; Vanecek, Jiri; Zemkova, Hana (Brain research. Molecular brain research, 2003)
In vivo melatonin serves as a feedback signal to the circadian pacemaker located in the suprachiasmatic nuclei (SCN) and in vitro it phase advances the circadian rhythm of electrical activity in pacemaker cells. However, the occurrence and nature of phase shifting in secretion by cultured SCN neurons has not yet been established. Here we studied the effects of melatonin on the pattern of spontaneous arginine vasopressin (AVP) release in organotypic SCN slices. This culture mimicked the in vivo circadian AVP secretory rhythm, with low release during the subjective night and with peaks in secretion during the middle of subjective day. The endogenous period of the AVP secretory rhythm in organotypic culture ranged between 23 and 26 h, with the mean period of 24.1 +/- 0.3 h. Melatonin (10 nM) had variable effects on the pattern of AVP secretion depending on time of its application directly to the medium with organotypic SCN slices. When introduced at circadian time 22, 2 and 6 (the times corresponding to the late night and early day), melatonin delayed the AVP secretory rhythm by 1-4 h. When applied at circadian time 10 (late day), however, melatonin advanced the AVP secretory rhythm by about 2 h. At other circadian times, melatonin was ineffective. These results indicate that melatonin exhibits the bidirectional phase-shifting effects on circadian secretory rhythm clock, which depends on the time-window of its application.
Keywords: Animals, Newborn; Male; Rats, Wistar; orgánové kultury - kultivační techniky; Arginine Vasopressin; mužské pohlaví; radioimunoanalýza; Suprachiasmatic Nucleus; potkani Wistar; melatonin; neurony; Organ Culture Techniques; arginin vasopresin; novorozená zvířata; cirkadiánní rytmus; Melatonin; Circadian Rhythm; krysa rodu Rattus; Time Factors; Animals; ženské pohlaví; Radioimmunoassay; nucleus suprachiasmaticus; zvířata; Neurons; Rats; časové faktory; Female